Management of pediatric cardiac surgery wound: a literature review - Prendin, Angela; Tabacco, Benedicta; Fazio, Paola Claudia; de Barbieri, Ilaria (Acta Biomedica Atenei Parmensis, 2021)
Background: Sternal wound infection is a severe complication of cardiac surgery in the pediatric population (0-18 years old) that can lead to increased morbidity, mortality, and prolonged hospitalization. Health professionals have the ability to perform some interventions during the pre, intra and post-surgery to correctly manage sternal wounds, with the goal of preventing infections. Objectives: To identify and discuss current best practice in the prevention, incidence, and treatment of infections of the cardiac surgery site in the pediatric population. Methods: Between February 20th 2021 and February 28th 2021 we consulted the PubMed database adopting full text, 20 years, Humans, English, Child aged 0 to 18 years as criteria. Twenty articles out of sixty-six were considered relevant to this study. These were divided into four themes. Results: All studies highlight the lack of standard guidelines for managing pediatric patients undergoing cardiac surgery. Some centers developed protocols for managing antibiotic prophylaxis supported by measurable interventions; others implemented infection surveillance systems involving families taking care of patients after hospital discharge. Discussions: the identification of healthcare-associated infections in the pediatric population after cardiac surgery is useful in all peri-operative phases. The limited and restricted literature connected to single centers, with relatively small sample sizes, the use of a single database. Conclusion: There is a lack of standard guidelines. The prevention of site infection ought to the goal of reducing surgical site infections. Building a network between the multidisciplinary staff and the pediatric patient’s family improves the infection surveillance system, reducing the incidence of infections.